Computation of consumer price indices: special problems (Geneva: International Labour Office, 1962)
This book is about the special problems of consumer price index.
Report prepared for the tenth International Conference of Labour Statisticians )Geneva, October 1962).
rpm 22/01/2019
Loans
Keywords: Consumer Price Indices; Consumers; Prices